Changes in hospital management of acute severe asthma by thoracic and general physicians in Birmingham and Manchester during 1978 and 1985. Issue 2 (February 1990) - Baldwin, D R; Ormerod, L P; Mackay, A D; Stableforth, D E
Abstract : Hospital management of acute severe asthma in 14 large hospitals in Birmingham and Manchester was audited in a random 20% of 1196 patients aged 15-45 years admitted in 1985. Of the 239 admissions randomised, 192 were suitable for study. Results were compared with those from a study in the same hospitals using the same methods in 1978. The age and sex of the patients and their smoking history, duration of asthma, and hospital attendance were similar in 1978 and 1985. A much smaller proportion of patients presented with symptoms of over seven days' duration in 1985 (8.5%) than in 1978 (26%). The inpatient management of asthma appears to have improved in both thoracic and general units, with more thorough functional assessments, more frequent performance of relevant investigations (arterial blood gases and peak expiratory flow rates) and more frequent use of recommended treatment (nebulised bronchodilators, oral and intravenous corticosteroids). Less difference was found in 1985 between units with a specialist thoracic interest and those without, though some differences remained in 1985 in monitoring of peak expiratory flow rate and arterial blood gases, outpatient prescribing, and follow up arrangements. Inhaled preventive medication was prescribed more frequently than in 1978. In 1985 there was a 56% increase in admissions for asthma. The proportion of severely ill patients was similar to that in 1978, but in the most severe functional grade mean arterial carbon dioxide tension was higher in 1985 and more patients were ventilated. Our results suggest that hospital management by thoracic and general physicians has improved over the period 1978-85. Patients presented earlier in 1985, though there seems to have been an increase in asthma of all grades of severity.